Efektivitas Pendidikan dan Perberdayaan Ekonomi di Pesantren Ibnu Kasim Nahdlatul Wathan Bintan - Firdaus Firdaus (TANJAK, 2021)
This study aims to examine the effectiveness of education and economic empowerment at the Ibnu Kasim Nadhatul Wathan Islamic Boarding School in improving student learning outcomes in terms of various supported aspects. The research method is descriptive qualitative based on the information obtained. Data collection techniques are carried out by interviewing elements of this pesantren, and observing learning activities, funding included in the economy of this pesantren, and developing the empowerment of personnel needed in this pesantren. Based on the results of the study, it shows that the application of educational effectiveness and economic empowerment at this pesantren is very good and suitable for increasing progress in this pesantren.